Safety and efficacy of intracoronary artery administration of human bone marrow-derived mesenchymal stem cells in STEMI of Lee-Sung pigs—A preclinical study for supporting the feasibility of the OmniMSC-AMI phase I clinical trial - Chen, Wannhsin; Hou, Chun-Hsiang; Chen, Yi-Ling; Shen, Hsin-Hsin; Lin, Chen-Hsuan; Wu, Cheng-Yi; Lin, Meng-Hsueh; Liao, Chih-Ching; Huang, Jun-Jae; Yang, Chi-Yu; Li, Yi-Chen; Yip, Hon-Kan (Frontiers in Cardiovascular Medicine, 2023)
Background This study tested whether early left intracoronary arterial (LAD) administration of human bone marrow-derived mesenchymal stem cells (hBMMSCs, called OmniMSCs) in acute ST-segment elevation myocardial infarction (STEMI) of Lee-Sung pigs induced by 90 min balloon-occluded LAD was safe and effective. Methods and results Young male Lee-Sung pigs were categorized into SC (sham-operated control, n = 3), AMI-B (STEMI + buffer/21 cc/administered at 90 min after STEMI, n = 6), and AMI-M [acute myocardial infarction (AMI) + hBMMSCs/1.5 × 107/administered at 90 min after STEMI, n = 6] groups. By 2 and 5 months after STEMI, the cardiac magnetic resonance imaging demonstrated that the muscle scar score (MSS) and abnormal cardiac muscle exercise score in the infarct region were significantly increased in the AMI-B than in the SC group that were significantly reversed in the AMI-M group, whereas the left ventricular ejection function by each month (from 1 to 5) displayed an opposite pattern of MSS among the groups (all p < 0.001). By 5 months, histopathological findings of infarct and fibrosis areas and isolectin-B4 exhibited an identical pattern, whereas the cellular expressions of troponin-I/troponin-T/von Willebrand factor exhibited an opposite pattern of MSS among the groups (all p < 0.001). The ST-segment resolution (>80%) was significantly earlier (estimated after 6-h AMI) in the AMI-M group than in the AMI-B group (p < 0.001). The protein expressions of inflammation (IL-1β/TNF-α/NF-κB)/oxidative stress (NOX-1/NOX-2/oxidized protein)/apoptosis (cleaved caspase-3/cleaved PARP)/DNA damage (γ-H2AX) displayed an identical pattern to MSS among the groups, whereas the protein expressions of angiogenesis factors (SDF-1α/VEGF) were significantly and progressively increased from SC, AMI-B, to AMI-M groups (all p < 0.001). Conclusion Early intra-LAD transfusion of OmniMSC treatment effectively reduced the infarct size and preserved LV function in porcine STEMI.